Advanced Numerical Methods in Applied Sciences - Iavernaro, Felice (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The use of scientific computing tools is currently customary for solving problems at several complexity levels in Applied Sciences. The great need for reliable software in the scientific community conveys a continuous stimulus to develop new and better performing numerical methods that are able to grasp the particular features of the problem at hand. This has been the case for many different settings of numerical analysis, and this Special Issue aims at covering some important developments in various areas of application.